Ecotoxicology of Microplastics with Interference in Human and Marine Ecosystems: A Mini Review - Soni, Sandeep Kumar; Solanki, Manoj Kumar; Pandey, Rajesh; Gautam, Ankit Kumar; Ojha, Saurabh; Singh, Anchal; Patel, Rohit; Mishra, Parikshit (International Journal of Scientific Research in Biological Sciences, 2023)
This review provides a comprehensive examination of the toxicological insinuations of microplastics, exploring its multifaceted impact in environment, marine ecology, and biological entities. Microplastics, pervasive in contemporary environments, pose a considerable threat to ecological balance. The assessment of environmental repercussions encompasses soil contamination, alteration of nutrient cycling, and disruptions in terrestrial and aquatic ecosystems. In marine environments, microplastics exert adverse effects on various life forms, influencing behaviour, reproduction, and community dynamics. Furthermore, the review delves into the complex pathways through which microplastics enter and interact with biological systems, and affects the metabolism and energy production, regulative processes, oxidation, neurological actions, cardiac responses, cardiovascular functions, pulmonary and liver function.